An Analysis of Trends in Female Labor Force Participation in Japan - Shimada, Haruo; Higuchi, Yoshio (Journal of Labor Economics, 1985)
Until recently, the aggregate female labor force participation rate in Japan has shown a secular declining trend throughout the postwar period of economic development. Participation of paid female employees alone exhibits a steadily rising trend, more or less comparable to that in the United States and European countries. Although the fertility rate dropped drastically shortly after World War II, in the subsequent period increases in female education and a relative improvement of female wages appear to have promoted a substantial increase in paid female employment. Labor supply equations for paid employees estimated from time-series data provide negative income and positive wage elasticities. Cross-sectional analysis gives reasonable results, particularly for middle-age wives. Absolute values of estimated wage elasticity, notably, have almost always been smaller than income elasticity, unlike many research findings in the United States.